Notes on the acoustic repertoire of Melanophryniscus klappenbachi Prigioni & Langone, 2000 - Kurth, Meike; Hörnes, David; Esser, Sascha; Rödder, Dennis (Zootaxa, 2013)
The genus Melanophryniscus Gallardo, 1961 currently comprises 25 recognized species (Frost 2012) arranged in three (Cruz & Caramaschi 2003) to four species groups (Cespedez & Motte 2001, quoted by Maneyro et al. 2008) on the basis of morphological characters. The Melanophryniscus stelzneri species group currently contains nine species, i.e. M. atroluteus (Miranda-Ribeiro, 1920), M. cupreuscapularis Céspedez & Alvarez, 2000, M. dorsalis (Mertens, 1933), M. fulvoguttatus (Mertens, 1937), M. klappenbachi Prigioni & Langone, 2000, M. krauczuki Baldo & Basso, 2004, M. montevidensis (Philippi, 1902), M. rubriventris (Vellard, 1947), and M. stelzneri (Weyenbergh, 1875). So far, advertisement calls of only four of these species have been described, i.e. those of M. atroluteus, M. dorsalis, M. krauczuki, and M. montevidensis (Kwet et al. 2005, Baldo & Basso 2004). Herein, we describe the courtship call and distress call of M. klappenbachi and compare it with the calls of other members of the group (for definitions of the respective call types see below).